Impact of an arbuscular mycorrhizal fungal inoculum and exogenous MeJA on fenugreek secondary metabolite production under water deficit - Irankhah, Simin; Chitarra, Walter; Nerva, Luca; Antoniou, Chrystalla; Lumini, Erica; Volpe, Veronica; Ganjeali, Ali; Cheniany, Monireh; Mashreghi, Mansour; Fotopoulos, Vasileios; Balestrini, Raffaella (My University, 2020)
Trigonella foenum-graecum (fenugreek) is a leguminous plant that produces secondary metabolites frequently used in medicinal and food preparation. Here, the role of an arbuscular mycorrhizal (AM) fungal inoculum, alone or in combination with methyl jasmonate (MeJA) chemical treatment, was evaluated on the production of trigonelline and diosgenin in fenugreek plants grown under mild water limitation. After inoculation, fenugreek plants were subjected to several combined treatments, i.e. well-watered (NS) and water-stressed (WS), both treated with different MeJA concentrations (0, 50, 100, 200 mL/L). At the end of the experiment, in addition to trigonelline and diosgenin content, an array of plant growth parameters (i.e. fruit, stem and root dry weights, fruit number) and biochemical stress markers (i.e. proline, nitric oxide, hydrogen peroxide, MDA) were examined. Results mainly showed a significant increase in production of the considered secondary metabolites, although they are differentially influenced by the individual factors (Stress, SYM, MeJA) and their interactions. SYM treatment was more effective on the production of trigonelline, independently from growth conditions, while diosgenin biosynthesis was influenced by the presence of root symbioses only in combination with MeJA treatment. A differential impact, depending on the applied treatment (inoculum, MeJA treatments, water deficit), on plant growth and on production of the considered bioactive molecules was revealed, providing new information on the effect of biological and chemical priming treatments.
Keywords: AM fungi; Drought; Fenugreek; MeJA; Symbiosis; Trigonella foenum-graecum